2022
DOI: 10.1111/jocd.15170
|View full text |Cite
|
Sign up to set email alerts
|

Plant polyphenols as green sunscreen ingredients: A systematic review

Abstract: The sun is the source of energy for living things on Earth. It emits electromagnetic radiation of various wavelengths including infrared, visible, and ultraviolet light. Ultraviolet radiation (UVR) is divided into three regions: UVA, UVB, and UVC. UVA region (320-400 nm) penetrates deep into the skin through the epidermis and dermis, which are responsible for skin darkening, photoaging, and DNA damage. UVB region (280-320 nm) acts mainly on the epidermis, which is the major cause of sunburn and skin cancer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…Plants are rich in polyphenols including phenolic and flavonoid compounds that may have the potential to develop as a skin-whitening agent in the cosmeceutical and pharmaceutical industry. 92 From Table 1, we concluded that the use of natural plants as skinwhitening agents is highly effective as there is a significant correlation between the content of polyphenol compounds and antimelanogenesis, antityrosinase, and antioxidant activities.…”
Section: Conclusion and Our Perspectivesmentioning
confidence: 99%
“…Plants are rich in polyphenols including phenolic and flavonoid compounds that may have the potential to develop as a skin-whitening agent in the cosmeceutical and pharmaceutical industry. 92 From Table 1, we concluded that the use of natural plants as skinwhitening agents is highly effective as there is a significant correlation between the content of polyphenol compounds and antimelanogenesis, antityrosinase, and antioxidant activities.…”
Section: Conclusion and Our Perspectivesmentioning
confidence: 99%
“…One study demonstrated that flavonoids and phenolic, which are antioxidants, have aromatic rings in their chemical structure that can absorb UVA and UVB radiation in the 200-400 nm wavelength range. As a result, they possess optical shielding characteristics and can be used as natural sunscreens 32 . Several other studies have shown a significant correlation between SPF and the phenolic and flavonoid content of nine medicinal plants 33 .…”
Section: Quantitative Concentrations Of Flavonoids and Phenolic Inmentioning
confidence: 99%
“…In recent years, consumer demand for utilizing natural botanical sources in cosmetics has grown substantially due to fewer side effects, high efficiency, and easy availability (Ng et al, 2022). Therefore, research shifted toward natural products with the difficult attempt to formulate stable topical emulsions containing natural bioactive constituents.…”
Section: Toward Eco-sustainable Luxury Productsmentioning
confidence: 99%